PERANCANGAN BAGGAGE HANDLING SYSTEM (BHS) DI YOGYAKARTA INTERNATIONAL AIRPORT - Raden Fatchul Hilal; Sudirman Hi Umar (Politeknik Penerbangan Surabaya, 2020)
In oder to support flight security and safety in an airport, the implementation of automated baggage handling systems (BHS) / Hold Baggage Screening (HBS) is very necessary to be able to minimize various airline baggage thefts. As an airport which is located in strategic area of tourism, education, and birocracy system, YIA is expected to accomodate the movements of passenger, cargo and large numbers of airplane. Passengers baggage handling, in its development, have major problems in the loading and unloading process so that automated Baggage Handling System (BHS)/Hold Baggage Screening (HBS) technology is very necessary to prepare so that airports no longer need to involve porters' hands to deal with the baggage problems.Based on the Decree of the Minister of Transportation number KP 1164 of 2013, Yogyakarta International Airport (YIA) is prepared to accomodate both domestic and international passenger movements of 20,000,000 pax/year, cargo movements of 55,380 tons/year, and aircraft of 131,830 aircraft/year. The purpose of this research is to design the Baggage Handling System (BHS) at Yogyakarta International Airport (YIA) as one of the airports that are planned to apply the aerotropolis airport concept. Furthermore, in conducting research, we emphasize Autocad application to create a two-dimensional framework and design, then continued with Solidworks3D software to create a three-dimensional design for the Yogyakarta International Airport (YIA) baggage handling system.We consider to run research in Yogyakarta International Airport (YIA), based on its vital roles that the airport was built to replace the roles of Yogyakarta Adi Sutjipto International Airport which had already experienced overcapacity and incosiderable to develop from both the technical aspect and its facilities and infrastructure. Based on the results of the study, the design of the study which was carried out with a baggage handling system (BHS) framework at Kuala Namu International Airport in Deli Serdang which is designed to have 7 stages starting from utilization for check-in checks, Out of Gauge (OOG) checks or baggage that has a weight and dimensions that exceeds the maximum size of baggage, X-Ray Checking MVXR 5000 ( Screening Level 1/2), Manual Coding Station (MCS), X-Ray Inspection RTT 110 (Screening Level 3/4), Examination by Avsec and Reconciliation Experts (Level 5/6), SCADA (Supervisor Control Data Acquisition).